Has Presidential Regulation No. 126 of 2022 Worked? - Anita Shalehah; Syafa Aulia Pradini; Budi Mulia; Rizki Tegar Sembada (Public Administration, Faculty of Politics and Social Science, Universitas Jenderal Soedirman, Indonesia, 2026)
This research aims to discuss the effectiveness of Presidential Regulation No. 126 of 2022 concerning the acceleration of national salt development to overcome Indonesia’s dependence on salt imports in 2022-2024 period. The regulation was designed to increase home production of salt to secure the country’s supply and cut reliance on imports. This research uses a qualitative descriptive approach with a literature review method through the analysis of policy documents, the official statistics of Statistics Indonesia and Ministry of Marine Affairs and Fisheries, and relevant literature. The analysis is based on the public policy framework developed by Thomas R. Dye, which includes the steps of problem identification, agenda setting, policy formulation, policy legitimacy, implementation, and evaluation. The results suggest that the regulation was developed through a comprehensive policy process consistent with Dye’s framework. However, the policy was not associated with a significant reduction in salt imports over the study period, even though it was systematically designed and implemented. These results imply that a good policy process cannot realize policy objectives without better implementation and domestic production capacity enhancement. The study contributes to the public policy literature by showing the importance of linking policy formulation with implementation outcomes. Future studies should incorporate primary data from relevant government institutions for a more holistic assessment of policy effectiveness